Genetic diversity in Pinus remota (Pinaceae) populations of Northeast Mexico: evidences of historical demographic contraction - González Jiménez, Aridahí; Delgado Valerio, Patricia; Molina Sánchez, Agustín; Flores López, Celestino; Vargas Gutiérrez, Juan Pablo; García Magaña, J. Jesús (Instituto de Ecología, A.C., 2021)
Background and Aims: The decrease and fragmentation of populations result in the loss of variation and increase in genetic differentiation. Pinus remota is an arboreal-shrubby species of restricted distribution with scattered and fragmented populations. The objectives of the present study were: to evaluate the levels of genetic variation, inbreeding and the effective size of the populations, to test the hypothesis of the existence of bottlenecks associated with the reduction of the genetic variation of the populations, and to analyze the genetic structure and its association with the geographic distribution of populations. Methods: The study was carried out in seven representative populations of their natural distribution in Mexico, by screening a total of 112 trees with five nuclear microsatellites. The data were evaluated with parameters of population genetics and Bayesian approach methods. Key results: The average expected heterozygosity (He=0.557) was higher than the observed heterozygosity (Ho=0.375). The populations are not in Hardy-Weinberg equilibrium, with significant inbreeding levels (FIS=0.259) and small effective sizes (Ne between 375-425). These are structured in three genetic groups (FST=0.158), with high values of the Mc index (0.186-0.283), suggesting ancestral demographic decline events (between 11,910 to 23,820 years ago), associated with the Pleistocene climate changes. Conclusions: The study showed that P. remota contains a considerable genetic variation, which is spatially structured and associated with ancestral bottlenecks. Moreover, it is confirmed that P. catarinae is its synonym. The species has been able to survive and adapt to local environmental conditions. With this knowledge conservation strategies for the remaining populations of the species are proposed.